2018
DOI: 10.1146/annurev-phyto-080615-100327
|View full text |Cite
|
Sign up to set email alerts
|

World Management of Geminiviruses

Abstract: Management of geminiviruses is a worldwide challenge because of the widespread distribution of economically important diseases caused by these viruses. Regardless of the type of agriculture, management is most effective with an integrated pest management (IPM) approach that involves measures before, during, and after the growing season. This includes starting with resistant cultivars and virus- and vector-free transplants and propagative plants. For high value vegetables, protected culture (e.g., greenhouses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(166 citation statements)
references
References 179 publications
1
139
0
4
Order By: Relevance
“…Table S3). These results suggest that, despite the greater distance between 34 sampled sites, some connection between the two regions exists, resulting in an incipient 1 pattern of differentiation. Sampling of intermediate regions between AL and MG may 2 provide a better picture of the genetic make-up of the BlYSV population.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Table S3). These results suggest that, despite the greater distance between 34 sampled sites, some connection between the two regions exists, resulting in an incipient 1 pattern of differentiation. Sampling of intermediate regions between AL and MG may 2 provide a better picture of the genetic make-up of the BlYSV population.…”
Section: Introductionmentioning
confidence: 81%
“…32 The DNA-A tree displayed the same topology as the DNA-B tree for the isolates from 33 Florestal, but isolates from Coimbra and Carandaí were not segregated ( Figure 2F). 34 Interestingly, the DNA-B of isolate BR-Flo01-14 from Florestal clustered together with 1 isolates sampled in Coimbra, due to a recombination event involving parental sequences 2 from these two locations (Suppl . Table S3).…”
Section: Introductionmentioning
confidence: 99%
“…Not known for NeVM and no marafivirus has been reported to be seedtransmitted (Dreher et al, 2012) No Not known for NeVM and no marafivirus has been reported to be pollentransmitted (Mink, 1995;Card et al, 2007 (Mink, 1995;Card et al, 2007;EFSA PLH Panel, 2013) Cannot be excluded Not known for PrGVA, but Geminiviridae are generally transmitted by insects (Rojas et al, 2018) …”
Section: Nomentioning
confidence: 99%
“…In 2018, approximately 59.7 thousand hectares were planted to tomatoes in the country, and 4.1 million tons of fruit was produced (Instituto Brasileiro de Geografia e Estatística [IBGE], 2018). Tomato production can be affected by several begomoviruses, the most prevalent being tomato severe rugose virus (ToSRV) (Fernandes et al, 2008;Inoue-Nagata et al, 2016;Rojas et al, 2018;Mituti et al, 2019). Begomoviruses are transmitted by the silverleaf whitefly Bemisia tabaci in a circulative-persistent manner (Rosen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%